HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF ENMETAZOBACTAM AND CEFEPIME - Nidhi Sahu; Udit Narain Soni (The Bioscan, 2025)
The present study aimed to develop and validate a simple, precise, accurate, and robust reverse-phase high-performance liquid chromatography (RP-HPLC) method for the simultaneous estimation of Enmetazobactam (EMB) and Cefepime (CFP) in bulk and pharmaceutical formulations. Chromatographic separation was achieved using a C18 Hypersil BDS column with an optimized mobile phase, resulting in sharp and well-resolved peaks for both analytes. The method exhibited excellent linearity within the concentration ranges of 5–25 μg/mL for EMB and 10–50 μg/mL for CFP, with correlation coefficients (r²) of 0.9987 and 0.9990, respectively. Accuracy studies revealed mean recoveries close to 100%, confirming the method’s reliability. Precision results showed %RSD values within acceptable limits for repeatability, intra-day, and inter-day analyses, while robustness tests indicated that minor variations in analytical conditions did not significantly affect the results. The method also demonstrated high sensitivity, with low LOD and LOQ values for both drugs. Assay of the marketed formulation showed drug content of 99.716% for EMB and 99.271% for CFP, indicating suitability for routine quality control. The validated method fulfills ICH Q2(R1) guidelines and is suitable for routine analysis, stability testing, and quality assessment of EMB and CFP in combined pharmaceutical dosage forms. KEYWORDS: Enmetazobactam; Cefepime, RP-HPLC, Method development, Validation, Linearity, Accuracy; Precision, ICH Q2(R1), Pharmaceutical analysis.